Descriptive problems in defining the category of copulas: syntactic and semantic distribution of the ingressive copulas VIRSTI and TAPTI - Mikulskas, Rolandas (Lietuvių kalba, 2018)
Cognitive Grammar (Langacker 1991) allows for a unified account of copular constructions. In this framework, all types of copular constructions can be seen as the different instantiations of a single archetype of statements of identity between two entities (Mikulskas 2017). Radical Construction Grammar, the framework adopted in this article, also allows for a unified account of copular verbs, as it views both so-called ‘semi-copulas’ and typical copulas as members of a single category of copulas as long as each of them fills the same slot between the thematic argument and the predicative complement in a copular construction. According to Radical Construction Grammar, an independent word class ‘copula’ does not exist. “Instead, verbs in a particular language can be labelled ‘copular’ if they have the appropriate semantics and morphosyntax to fit in the so-called ‘copular slot’ of a copular construction” (Petré 2012: 30). From this theoretical perspective, the term ‘copula’ applies only derivatively. Thus, syntactically, copular verbs have a linking function. Additionally, some of them express various aspectual meanings and can be seen as aspectual variants of the typical copula “be”. For instance, the Lithuanian verbs tapti ‘become’, virsti ‘turn into’, darytis/pasidaryti ‘become’ (lit. ‘make oneself’) and, formerly, stotis/pastoti ‘become’ (lit. ‘stand up’), mainly in the Simple Past and Future tenses, when used in copular constructions, express ingressive aspect of the change event. These verbs, used in different constructions, such as existential, locomotional etc., retain their original meaning. Importantly, even when they are used in copular constructions, while being first of all linking verbs and aspectual markers, they can still have different syntactic and semantic properties. The latter are the outcome of their primary meanings inherited from their source constructions (‘backward pull’; Traugott 2008). That said, it is nevertheless clear that each of these verbs is in a different stage on its way to grammaticalization and each accommodated to copular function in a varying degree. So, a descriptivist encounters a practical problem: which of the above-mentioned verbal lexemes qualify as ‘real’ copulas and which do not? Are such verbs as augti ‘grow’ or eiti ‘go’, which can perform copular function in certain restricted contexts, on a par with more typical copulas such as tapti or virsti? Some Lithuanian researchers even doubt if the verb lexeme virsti can be labelled ‘copular’. To provide for this descriptive need a definition of the category of copulas is elaborated in the first two chapters of the article. Complementing the constructional requirement of filling the slot between the thematic argument and the predicative complement, two additional criteria are suggested. First, the postcopular nominal, as the result of reanalysis of the source construction in the course of grammaticalization, must become coreferential with the subject nominal. This is a necessary but not sufficient condition, as it does not differentiate between primary and secondary predicatives. Secondly, the types of complement of the verb must be unpredictable from its semantics or, in other words, the copular verb must be desemanticized to a sufficient degree to be capable of selecting its complements from a wide array of semantic and syntactic types (that is, NP, ADJ, PP). So the question whether to include a concrete verb lexeme into the class of copulas is mainly reduced investigating the semantics of its complements (or the productivity of its complementation). In the second two chapters of the article a contrastive study of the syntactic and semantic properties of the copular verbs virsti vs. tapti is presented in order to prove that the corresponding copular constructions featuring these verbs are different instantiations of the more abstract ingressive-aspect-expressing construction. A quantitative analysis of data in the Corpus of Modern Lithuanian reveals various relevant points in the parallel development and interaction of these verbs and in their coexistence in present-day Lithuanian: how they divide between them the job of expressing ingressive aspect in the profiled change events while at the same time competing with each other in some contexts. Additionally, some relevant facts of the usage of the copulas under discussion were checked in the Old Lithuanian Corpus and in the Dictionary of the Lithuanian Language. The analysis allows us to draw some important conclusions concerning the coexsistence of the two verbs under discussion and their categorial status in modern Lithuanian. First of all, the verb virsti can reasonably be seen as an aspectual variety of the copula būti ‘be’, on a par with the more grammaticalized copula tapti. The verb virsti, when used in copular constructions, is sufficiently desemanticized: one may claim that a sufficient number of copular constructions featuring the verb virsti have nearly lost their touch with their inherent semantics. More specifically, half of the analysed cases of copular constructions with this verb have already abandoned their tendency – inherited from the locomotional source construction (designating the overturning of a vertical object ) – to denote negatively evaluated change events. Though the verb virsti was originally used mainly in the inclusive type of copular constructions, it is now, on the analogy of copular constructions featuring the verb tapti, increasingly used in the ascriptive type as well: in more than 4% of the analysed instances the copula virsti selects adjectival predicative complements. Sporadically, the copula virsti is attested even in the specificational type of copular constructions (in this type of sentences the usage of the copula tapti is unrestricted). Also in modern Lithuanian the copula virsti has borrowed from the copular constructions featuring tapti the morphosyntactic coding of its complements by the instrumental instead of the original coding with PP. A thorough study of the semantic distribution of the copulas virsti and tapti in the Corpus of Modern Lithuanian shows that they have more or less divided between them the semantic space of aspectual expression according to the meanings they have inherited from their source constructions, and to their resulting aspectual potential. The constructions containing the copula virsti profile, in most cases, a radical transformation of a subject referent proceeding in an uncontrolled and incremental way. Such transformations include changes of physical elements, changes in a person’s mood and character, or spell-induced changes in fairy tales. Aspectually, such copular constructions have the profile of an accomplishment. Conversely, the constructions featuring the copula tapti presuppose a subject referent in control of the profiled change event. The result of the change is usually a new social status, a new profession or office held by the subject referent. In some cases the change profiled is only a projection of some relevant features of the subject referent into the cognitive domain of some speech community: the subject referent of the sentence, because of its social behaviour or personal features, is declared by the speaker to be a model or a guide for other people. The aspectual profile of such constructions is typically that of an achievement as in most cases they designate an instantaneous ingression of the subject referent into its new status. Nevertheless, the quantitative analysis of the corpus data shows that in about 13% of the copular constructions analysed the preterite verbal forms virto and tapo can be used interchangeably. This fact, considered together with the empirically attested facts of mutual interaction of the corresponding copular constructions, allows us to treat the constructions featuring these copular forms as two different instantiations of a single copular construction expressing the ingressive aspect of the profiled change event.